Design and simulation of a controller for an active suspension system of a rail car. Issue 1 (1st January 2018) - Daniyan, I. A; Mpofu, K.; Osadare, D. F.
Abstract: The quest to increase the performance of rail car in terms of stability, safety and ride comfort has triggered research into the design, modelling and dynamic simulation of the suspension system of a rail car. Advance control and automation techniques can be used to optimize the performance of a rail car suspension system. This work introduces the mathematical model of two-degree-of-freedom and the use of the conventional proportional integral as well as derivative (PID) controller for the active suspension system of a rail car. Dynamic simulation via the use of MATLAB Simulink environment was employed for the design and analysis of the effect of the controller with the control algorithm of PID controller used to reduce motion of rail car body and the damper. The dynamic model for the linear rail car suspension system was formulated while the PID controller type was used to test the system's performance while the Ziegler–Nichols tuning rules were used to determine proportional gain, reset rate and derivative time of PID controllers. The results obtained show that the developed controller is highly efficient. The simulated results of the comparison between the passive suspension system and the active suspension system proved that, active suspension system with PID control improves ride comfort, gives lower or almost no peak over shoot (amplitude) and faster settling time compared to the passive suspension system. This enhances safety, good comfort for drivers and passengers as well as isolation of railcar from noise, vibration and other disturbances.